Sistem Informasi Pemerintah Daerah Dalam Pelayanan Berbasis E-Government Kabupaten Banggai Laut (Studi Kasus Dinas Kependudukan Dan Pencatatan Sipil) - Bode, Andi; Udilawaty, Siska; Harun, Rofiq; Talodo, Moh. Arif N (Journal Of Informatics And Busisnes, 2024)
The Population and Civil Registration Service of Banggai Laut Regency is a regional government agency that serves the community, one of which is civil registration of population in the issuance of documents. Currently, the Department of Population and Civil Registration still uses a manual system to carry out the recording process. Before issuing the birth certificate quotation document, the applicant must register manually, in this case it is considered ineffective in providing public services. To overcome the above, it is necessary to create a new system, namely a web-based public service information system that can be accessed online by the public, so that it is hoped that it can simplify administration for the people of Banggai Laut, especially those who live on the islands. So the use of information technology as a media source for public administration services that are fast and easy to understand can be a solution for optimizing the population administration service process in Banggai Laut Regency. Based on these problems, making the creation of a Regional Government Information System in E-Government Based Services in Banggai Laut Regency (Case Study of the Population and Civil Registration Service) is the right solution in public services to make it easier for the public to manage population administration and civil registration to make it more effective and efficient.